Steric effects of alkyl dibenzothiophenes: The root cause of frustrating efficacy of heterogeneous desulfurization for real diesel. Issue 5 (31st January 2022) - Li, Ao; Song, Hongyan; Meng, Hong; Lu, Yingzhou; Li, Chunxi
Abstract: High‐carbon alkyl dibenzothiophenes (DBTs) in real diesel are difficult to remove. Their steric effect has been studied and identified as the controlling factor in heterogeneous catalytic oxidation desulfurization (ODS) process. Mixed alkyl DBTs (C2 ‐DBT, C2 ‐C2 ‐DBT, C3 ‐DBT, and C3 ‐C3 ‐DBT) were synthesized via DBT's Friedel–Crafts alkylation, and their reactivity is DBT > C2 ‐DBT > C2 ‐C2 ‐DBT > C3 ‐DBT > C3 ‐C3 ‐DBT. C3 ‐DBT, C2 ‐C2 ‐DBT, and C3 ‐C3 ‐DBT can be hardly removed by any of three efficient heterogeneous ODS processes, but are removed efficiently in a homogeneous ODS process of HAc‐HPW‐H2 O2, which contrasts the great importance of their steric effects in heterogeneous catalytic process. Thus, the frustrating efficacy of various ODS processes for real diesel is likely originated from the unidentified high‐carbon alkyl DBTs and their least reactivity in heterogeneous catalytic systems. And, the steric hindrance is diminished greatly in a homogeneous catalytic process. The results are instructive for the development of new catalysts and catalytic ODS processes for real diesel.